Bacteriophages against Salmonella enterica: challenges and opportunities - Segundo-Arizmendi, Nalleyt; Flores-Coria, Alejandra Paola; Gómez-Garcia, Janeth; Hernández-Baltazar, Efrén; Meneses-Acosta, Angélica (Frontiers in Bioengineering and Biotechnology, 2025)
Salmonella spp. is the most common pathogen transmitted to humans through contaminated water and food. Due to its ability to infect both animals and humans, as well as the spread of antibiotic-resistant strains, this pathogen has become a priority for food and pharmaceutical industries. Consequently, research and development of treatments to combat infections caused by Salmonella spp. are ongoing. One of the most promising strategies is the phage therapy (PT) which is based on the use of very specific viruses that infect this pathogenic bacterium without any action over the host and which use has shown effectiveness. Now a days, at least 41 companies worldwide market phage therapy products mainly for use in the food sector to reduce the transmission chain of Salmonella spp. to humans. However, the complex production processes required to ensure product quality, stability, safety, and efficacy, as well as the need for regulatory frameworks for phage therapy, present limitations to the global application of this strategy seems to be a limitation to promote its use all over the world as a pharmaceutical product. Thus, this work presents a literature review on state-of-the-art of PT, analysing the opportunities and challenges that are present to consider such a therapy as an emerging treatment for antibiotic resistance of Salmonella enterica.